A PHENOMENOLOGICAL MODEL FOR ANALYSIS OF SOCIAL REPRESENTATIONS OF DEATH - N A Borisov (RUDN Journal of Philosophy, 2017)
The author makes an attempt to create a model for analysis of social representations of death based on phenomenological methodology. The main objects of analysis are the event of death as a spatial dimension of the representations and the image of death as their extension in time. Taking into account the shortcomings of existing models in the study of attitudes to death, the new model provides an analysis of the social aspects of religious and atheistic representations of death. The social representations are divided into elitist, mass and marginal. Phenomenological modeling includes four stages along with special method for each one. Consequently, the proposed model allows to understand both the attitudes to death at a certain historical period and social as such in a time and space of previous historical epochs, of the present life and of future interactions.